Time-Course Stress Response among the Disaster-Relief Workers Affected by the Great East Japan Earthquake - Kanoya, Yuka; Shoji, Masae; Honda, Yukiko (Journal of Japan Society of Nursing Research, 2019)
We assessed the stress response of 139 disaster-relief workers who were affected by the Great East Japan Earthquake. The assessment was conducted in two phases-three months and one year after the earthquake-using the Impact of Event Scale-Revised (IES-R). We investigated the association between the subjects' stress response and the status of those who experienced damage as a result of the earthquake. The results indicated that the subjects who were at high-risk for posttraumatic stress disorder (PTSD) were over 40% in both phases. The IES-R score was significantly higher among subjects who were staff members at the nursing department; who experienced the loss of family, friends, or their home; and who mentioned "safety of family" as the stress-related issue. To conclude, our findings reveal that the disaster-relief workers who were affected by the earthquake need long-term mental health support. Furthermore, the findings suggest that regular psychological training before and an appropriate working environment after disaster strikes need to be provided for the subjects.